The evolution of open‐source mobile applications: An empirical study. Issue 7 (9th March 2017) - Li, Deguang; Guo, Bing; Shen, Yan; Li, Junke; Huang, Yanhui
Abstract: Now, mobile applications grow at an exponential speed and their evolution activities are very active, while there is little research on the evolution of mobile apps. To have a better understanding of the evolution of mobile apps and find similarities or patterns in their evolution process, we conduct an empirical study on long spans in the lifetime of 8 typical open‐source mobile apps, which covers 348 official releases. First, we try to verify whether Lehman's laws still apply to mobile apps or not, extract a variety of metrics of the apps, and use statistical hypothesis testing to validate these laws. We find enough data that support a subset of Lehman's laws, while the rest do not. Second, we make some novel observations, eg, the growth of mobile apps is nonsmooth, and some versions of the apps have a great growth in their evolution. Enough data confirming that software instability increases great with the addition of third‐party method invocations, and automatic build and manage tool based on contract is introduced into project as apps continue evolving. Abstract : The growth of mobile apps is nonsmooth, and some versions of the apps grow great in their evolution Enough data confirming that software instability increases great with the addition of third‐party method invocations, and automatic build and manage tool based on contract is introduced into project as apps continue evolving.